Evaluasi dan Pengembangan Kebijakan Pendidikan di MAN 2 Deli Serdang - Muhammad Iqbal; Diva Pratama Rambe; Fitri Mushliha Simatupang; Mhd. Irgi Fahreza; Rizky Mutia Annisa (Peneliti.net, 2023)
The article entitled